2010
DOI: 10.14411/eje.2010.073
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Poecilimon ornatus group (Orthoptera: Phaneropteridae) with particular reference to the taxa in Bulgaria and Macedonia

Abstract: Abstract. The Poecilimon ornatus group has an exclusively European distribution and includes the largest species in the genus. A revision of the taxa belonging to this group in Bulgaria and Macedonia (Central and Eastern Balkan Peninsula) is presented. Nine taxa described from Bulgaria are synonymised with 3 previously known species, as follows: Poecilimon ornatus (= P. mistshenkoi marzani, syn. n., P. mistshenkoi tinkae, syn. n., P. mistshenkoi vlachinensis, syn. n.), P. affinis s. str. (= P. mistshenkoi mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…In bush-crickets, the songs of closely related species, especially those that speciated in allopatry, usually have a lineage-specific amplitude-temporal pattern that enables recognition for systematic purposes and for drawing conclusions about paths of speciation (e.g., Heller 1990Heller , 2006Chobanov and Heller 2010). In Tettigonia, differences between species have been observed in the time and frequency domains, while particular song-recognizing mechanisms may depend on the geographic and ecological preferences of the species (Schul 1994;Schul et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In bush-crickets, the songs of closely related species, especially those that speciated in allopatry, usually have a lineage-specific amplitude-temporal pattern that enables recognition for systematic purposes and for drawing conclusions about paths of speciation (e.g., Heller 1990Heller , 2006Chobanov and Heller 2010). In Tettigonia, differences between species have been observed in the time and frequency domains, while particular song-recognizing mechanisms may depend on the geographic and ecological preferences of the species (Schul 1994;Schul et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, phylogenetic signal should be accounted for in order to fully understand the relationship between pair-forming behaviour and spermatophore size variation across species [35 -37]. While male searching is likely to have evolved independently in Poecilimon at least four times (P. propinquus group, P. ornatus group, P. pergamicus group and P. heroicus group [10,22,24,25,38]), insufficient data currently exist on phylogeny and spermatophore size for a comparative analysis using phylogenetically independent contrasts of Poecilimon taxa that differ in searching behaviour. However, while accounting for ancestry and body mass among a smaller group (23) of Poecilimon species for which phylogenetic relationships are known, a recent study [39] found a significant relationship between spermatophylax mass and ampulla mass.…”
Section: Empirical Methodsmentioning
confidence: 99%
“…Local faunistic information has been reported by Chobanov [26] and Micevski et al [27] and the to-date information on Orthoptera of Macedonia has been critically summarized by Chobanov & Mihajlova [4]. In addition, three new species have been described from the territory of this country by Chobanov & Heller [28], Karaman et al [29] and Chobanov et al [30], some faunistic records were added by Lemonnier-Darcemont [31], Chobanov et al [32] and a "Red list of Orthoptera of the Republic of Macedonia" was published by LemonnierDarcemont et al [33]. Thus, currently the number of recognized species for Macedonia is 171 (with two additional subspecies).…”
Section: Introductionmentioning
confidence: 99%